Some Factors for Forming the Readiness of Prospective Teachers for Academic Mobility (Journal of Educational Sciences, 2025)
Undoubtedly, the changes taking place as a result of the society's entry into the global community require competitive high-quality specialists. Such changes are directly related to the field of education, including the training of future teachers, because the status of the teacher is highly valued in the country, and laws and concepts are adopted at the state level. This necessitates the training of a flexible, mobile, professional, adaptable and competent specialist who can compete in accordance with the ongoing changes in the international arena. Academic mobility is a key step in a prospective teacher's professional and academic growth. The purpose of this paper is to identify several factors influencing future teachers' readiness for academic mobility. To achieve the set goal, a qualitative research method was used, which included a theoretical analysis of the problem, as well as a focus group interview, with responses recorded and coded. The identified results were discussed, institutional, curricular, and professional factors of future teachers' readiness to undergo academic mobility were determined and analyzed. We expect that the proposed factors would allow future teachers to prevent obstacles in their academic mobility. The issue presented in the article may encourage other researchers to focus on various large-scale solutions for preparing future teachers for academic mobility in higher education institutions. Key words: academic mobility, future teacher, training, institutional, curricular, and professional factors.